Saline-water bioleaching of chalcopyrite with thermophilic, iron(II)- and sulfur-oxidizing microorganisms. - Watling, H.; Collinson, D.; Corbett, Melissa; Shiers, D.; Kaksonen, A.; Watkin, Elizabeth (2016)
The application of thermoacidophiles for chalcopyrite (CuFeS2) bioleaching in hot, acidic, saline solution was investigated as a possible process route for rapid Cu extraction. The study comprised a discussion of protective mechanisms employed for the survival and/or adaptation of thermoacidophiles to osmotic stress, a compilation of chloride tolerances for three genera of thermoacidophiles applied in bioleaching and an experimental study of the activities of three species in a saline bioleaching system. The data showed that the oxidation rates of iron(II) and reduced inorganic sulfur compounds (tetrathionate) were reduced in the presence of chloride levels well below chloride concentrations in seawater, limiting the applicability of these microorganisms in the bioleaching of CuFeS2 in saline water.